2005
DOI: 10.1111/j.1464-5491.2005.01660.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of ketoacidosis in Type 2 diabetes mellitus

Abstract: At the time of hospital presentation, the predominant mechanism for ketosis in KPDM2 is likely to be greater insulinopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…Indeed, patients presenting with diabetic ketoacidosis in Europe usually have type 1A diabetes; of 4807 patients admitted with ketosis-prone diabetes (KPD) in Denmark between 1996 and 2002, only 12% were subsequently classified with type 2 diabetes [5]. Not everyone with diabetic ketoacidosis is young, has autoimmune features or, with time, turns out to be insulin-dependent [6][7][8][9][10][11]. The lack of flexibility in the current classification system fails to pigeonhole these cases.…”
Section: Have No Name For That! Feeling Is All In All;mentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, patients presenting with diabetic ketoacidosis in Europe usually have type 1A diabetes; of 4807 patients admitted with ketosis-prone diabetes (KPD) in Denmark between 1996 and 2002, only 12% were subsequently classified with type 2 diabetes [5]. Not everyone with diabetic ketoacidosis is young, has autoimmune features or, with time, turns out to be insulin-dependent [6][7][8][9][10][11]. The lack of flexibility in the current classification system fails to pigeonhole these cases.…”
Section: Have No Name For That! Feeling Is All In All;mentioning
confidence: 96%
“…Patients with KPD have severe insulin deficiency at presentation, but can subsequently recover their insulin secretion [6,11,12]. LADA patients, in comparison with type 1 diabetes, have higher insulin levels [54].…”
Section: Insulin Secretion and Sensitivitymentioning
confidence: 99%
“…However, the mean BMI as well as the triglycerides were lower in our patients than levels reported in other studies [13,14], probably because of a lower rate of insulin resistance in our population. Moreover, the presence of the metabolic syndrome is more frequently associated with preserved β-cell function, and consequently a better glycaemic control after the acute episode and long-term remission [14,15]. In this kind of type 2 diabetes, the acute β-cell failure inducing ketosis [15] seems to be linked to a genetic propensity to glucotoxicity and lipotoxicity [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the presence of the metabolic syndrome is more frequently associated with preserved β-cell function, and consequently a better glycaemic control after the acute episode and long-term remission [14,15]. In this kind of type 2 diabetes, the acute β-cell failure inducing ketosis [15] seems to be linked to a genetic propensity to glucotoxicity and lipotoxicity [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…In the largest study of DKA in type 2 diabetics, Linfoot 11 found, using c-peptide concentration as a marker for insulin, a significant decrease in plasma…”
mentioning
confidence: 99%